Pelatihan English for tourism guna peningkatan interaksi sosial dan self-confidence bagi komunitas pariwisata - Chairina Safarina Wardani; M. Taufik Kautsar; Dini Lutfia; Sekar Larasati Lilo Sungkono (University of Muhammadiyah Malang, 2022)
As a tourism place, Jodipan Colorful Village is not only visited by domestic tourists, but also foreign tourists. On the one hand, the English language skills of teenagers around Kampung Warna-wani Jodipan are still very limited. Most teenagers there also tend to feel insecure when it comes to interacting with foreign tourists. In response to this, the service staff conducted an English for Tourism Training for six days to ten youths in Colorful Village. Service activities consist of psychoeducation to increase self-confidence and English for tourism training to improve English language skills in tourist areas. The results of the evaluation showed an increase in both self-confidence and English language skills in service participants.